Examining the Relationship Between Social Media-Based Marketing Variables and Research and Development Policies - Najafi, Mohammad Hasan; Mehrmanesh, Hasan; Kabaran Zad Ghadim, Mohammad Reza (Business, Marketing, and Finance Open, 2024)
The present study aims to examine the relationship between social media-based marketing variables and research and development policies. The statistical population in the quantitative section consists of home appliance marketers across the country, and given its unlimited nature, the sample size was determined to be 384 individuals. The participants were selected using a simple random sampling method. A standardized questionnaire was used to measure the variables. The validity of the questionnaire was assessed through confirmatory factor analysis, and its reliability was examined using Cronbach’s alpha coefficient. The research model was tested based on the structural equation modeling method using PLS software. The results of data analysis indicated that business strategy factors have a significant impact on research and development policies. Supportive policy factors have a significant impact on research and development policies. Business investment factors have a significant impact on research and development policies. Infrastructure factors of businesses also have a significant impact on research and development policies. Additionally, the significant impact of customer factors, business transformation factors, knowledge capital, and technological factors on research and development policies was confirmed.